Student-Generated Discussion in the Senior Secondary English Classroom - A.W. Lehmann (Networks: An Online Journal for Teacher Research, 2000)
The purpose of this research study was to devise and test a method of encouraging, and subsequently managing, student-generated discussion of English literature within a senior secondary classroom. The students would provide not only the discussion itself, but also a "client's-eye" evaluation of the process. Accordingly, students were engaged in part of the initial clarification of the study's purposes and procedures, produced the bulk of the discussion which constituted the content for the method being examined, and provided a post-discussion evaluation which could be compared to earlier comments. A simple qualitative analysis of written comments provided by the students and of my own notes and reactions to the discussion allowed me to define more clearly some observations about the dynamics of discussion and to select some directions for further investigation. It would be premature to draw any definitive conclusions based on this study alone, but some of the observations are constructively suggestive.